2012
DOI: 10.1002/jcu.21969
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of liver fibrosis by investigation of hepatic parenchymal perfusion using contrast‐enhanced ultrasound: An animal study

Abstract: This animal study showed that CEUS has the potential to be a complementary imaging tool in the evaluation of liver fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Studies had shown that CEUS is an accurate method for distinguishing severe and benign liver fibrosis . The liver is an organ in which blood is supplied by both hepatic artery and portal vein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies had shown that CEUS is an accurate method for distinguishing severe and benign liver fibrosis . The liver is an organ in which blood is supplied by both hepatic artery and portal vein.…”
Section: Discussionmentioning
confidence: 99%
“…Studies had shown that CEUS is an accurate method for distinguishing severe and benign liver fibrosis. 6,22 The liver is an organ in which blood is supplied by both hepatic artery and portal vein. At the stage of liver fibrosis, an extrahepatic shunt has not formed yet, and the characteristics of microcirculation changes are mainly intrahepatic shunt: First, there is formation of an abnormal connection between the portal vein and hepatic vein; then, there is a short-circuit artery-vein short shunt from the formation of the connection between the artery and vein because of the reconstruction of the hepatic lobule in liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…The DPI, defined as the maximum echo decibel of the TIC, assesses the perfusion of organs. In animal model, Ying M et al showed that the measurement of the liver parenchymal DPI was helpful for the evaluation of liver fibrosis, and the DPI decreased with advancing stages of fibrosis [24]. Atri M et al found that the DPI increased significantly in malignant renal masses compared to benign with visible changes in vascularity [25].…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, we initially identified the spleens of the rats with grey-scale ultrasound, and on the basis of these findings, we firstly evaluated the splenic haemoperfusion with colour Doppler ultrasound. Then, we switched the sonographic unit to the contrast-tuned imaging mode, and an ultrasound contrast agent (SonoVue, Bracco International, Amsterdam, the Netherlands) at a dose of 0.1 ml/kg was administered as a bolus into the caudal vein of the rat, followed by a 0.15 ml saline flush [ 31 , 32 ]. Immediately after injection, continuous scanning of the spleen was conducted to evaluate further the splenic haemoperfusion.…”
Section: Methodsmentioning
confidence: 99%